PENGARUH MEDIA SOSIAL TERHADAP PENURUNAN AKHLAK DAN MENURUNNYA ETIKA MORAL PADA GENERASI MUDA - Indramaya, Selpi; Masvi Rizkyah Rahmah; Ririn; Raja Nella Kusuma Dewi; Dian Amalia Syafitri; Ana Shofia Andriani; Muhammad Fikri Alamsyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The widespread use of social media among Indonesian adolescents raises serious concerns about the weakening of moral and social ethical values among the younger generation. This study aims to analyze the influence of social media on the decline of adolescent morality and Islamic character, while formulating relevant preventive solutions. A mixed methods approach was applied using an online questionnaire administered to 21 respondents from diverse groups and semi-structured interviews with teachers, parents, university students, and adolescents. Quantitative findings show that 57.1% of respondents considered digital content highly influential in reducing courtesy, 52.4% confirmed the normalization of offensive language in comment sections, and 85.7% concluded that adolescents remain highly vulnerable to negative trends. Qualitatively, findings revealed a personal integrity crisis, rising individualistic attitudes, and family conflicts driven by digital lifestyle pressures. This study affirms that parental supervision, age-based device restrictions, and religious value internalization are the most fundamental preventive defenses for youth morality in the digital age.